Determinants of R & R programme Participation among Coconut Producers in Tamil Nadu: A Heckman Two Stage Selection Approach - Narmadha, N.; Karunakaran, K.R.; Kandeepan, A. (Journal of Plantation Crops, 2024)
The purpose of the study is to investigate the variables that affect coconut farmers' participation in Tamil Nadu's Replanting and Rejuvenation (R & R) scheme. Utilising a multi-stage sampling technique, a total of 120 coconut farmers were surveyed as respondents. Heckman's two-stage model was used with Probit model included in the first stage, and OLS was used to analyse the income regression in the second stage. Results reveal that age of farmer, education, farming experience, awareness of R&R programme, age of coconut tree, high incidence of pest and diseases, availability of irrigation facilities, and availability of credit for purchasing farm inputs are the most important determining factors for participation. These findings suggest that the R&R program requires to be implemented on a large scale with the aid of Coconut Development Board. This program should focus on removing old, senile, unproductive, and disease-advanced palm trees, replanting them with quality seedlings at subsidized prices, and revitalizing existing gardens through an integrated set of practices.